2022
DOI: 10.3390/molecules27217339
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ε-caprolactone)-Based Graft Copolymers: Synthesis Methods and Applications in the Biomedical Field: A Review

Abstract: Synthetic biopolymers are attractive alternatives to biobased polymers, especially because they rarely induce an immune response in a living organism. Poly ε-caprolactone (PCL) is a well-known synthetic aliphatic polyester universally used for many applications, including biomedical and environmental ones. Unlike poly lactic acid (PLA), PCL has no chiral atoms, and it is impossible to play with the stereochemistry to modify its properties. To expand the range of applications for PCL, researchers have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…182 Researchers reported that the degradation rate of PCL can be controlled by adjusting the ratio of d , l -lactide to ε-caprolactone monomers in PCL- co -PLA copolymer. 183 Copolymer with higher lactide content degrades more rapidly due to the higher susceptibility of the lactide monomer to hydrolysis. The monomeric composition of polyhydroxyalkanoate (PHA) copolymers also affects their degradation behavior.…”
Section: Hydrolytic Degradation Of Biopolyestersmentioning
confidence: 99%
“…182 Researchers reported that the degradation rate of PCL can be controlled by adjusting the ratio of d , l -lactide to ε-caprolactone monomers in PCL- co -PLA copolymer. 183 Copolymer with higher lactide content degrades more rapidly due to the higher susceptibility of the lactide monomer to hydrolysis. The monomeric composition of polyhydroxyalkanoate (PHA) copolymers also affects their degradation behavior.…”
Section: Hydrolytic Degradation Of Biopolyestersmentioning
confidence: 99%
“…However, high modulus commercial PLA can be regarded as macromonomer copolymerized with low molecular weight comonomers [109]. PLA-based graft copolymers can be synthesized with monomers like ε-caprolactam [110], glycolic acid, polymers such as PEG [111], inorganic materials like CNTs, graphene oxide and natural macromolecules like dextran starch, chitosan, lignin, cellulose, silk sericin.…”
Section: Graftingmentioning
confidence: 99%
“…[16,17] PCL exhibits excellent biocompatibility, biodegradability, and processability, and has been approved by the FDA with a high biodegradation rate in the human body. [18] It has been adopted in widespread applications, such as biomaterials, biomedicine, ecological products, and packaging. [19][20][21] Despite its considerable degradability in various environments (such as soil, rivers, and oceans), PCL still requires specific conditions for decomposition to occur.…”
Section: Introductionmentioning
confidence: 99%